Revision of the genus Polistes Latreille (Hymenoptera: Vespidae: Polistinae) in the Philippine Islands - Selis, Marco (Zootaxa, 2018)
A taxonomic study on the paper wasp genus Polistes Latreille, 1802 from the Philippine Islands is presented. Three new species of the subgenus Polistella Ashmead, 1904 are described: P. (P.) esperanzae sp. nov., P. (P.) flavitarsis sp. nov., and P. (P.) tenuipunctatus sp. nov.. Polistes (Gyrostoma) tenebricosus nigrosericans Bequaert, 1940 is raised to species rank (P. (G.) nigrosericans stat. nov.). The Philippine subspecies of P. (P.) stigma (Fabricius, 1793) are synonymized under the typical form (= P. stigma alagari Petersen, 1987 syn. nov., = P. stigma dubius de Saussure, 1867 syn. nov., = P. stigma manillensis de Saussure, 1854 syn. nov.), and P. (P.) philippinensis funebris Bequaert, 1940 is synonymized under P. (P.) philippinensis de Saussure, 1854. A key to species of the genus from the Philippine Islands and new distributional records are provided.